Stripe Rust Effector Pst_9302 Inhibits Wheat Immunity to Promote Susceptibility - Haibin Zhao; Jiangyu Huang; Xiaoyan Zhao; Ligang Yu; Xiaodong Wang; Congcong Zhao; Hojjatollah Rabbani nasab; Chunlei Tang; Xiaojie Wang (Plants, 2023)
Puccinia striiformis f. sp. tritici is an obligate biotrophic fungus that causes destructive stripe rust disease in wheat. During infection, Pst secretes virulence effectors via a specific infection structure—the haustorium—inside host cells to disturb host immunity and promote fungal colonization and expansion. Hence, the identification and functional analyses of Pst effectors are of great significance in deciphering the Pst pathogenicity mechanism. Here, we identified one candidate Pst effector Pst_9302 that could suppress Bax-triggered cell death in Nicotiana benthamiana. qRT-PCR analyses showed that the transcript levels of Pst_9302 were highly increased during the early infection stages of Pst. The transient expression of Pst_9302 in wheat via the type-three secretion system (T3SS) significantly inhibited the callose deposition induced by Pseudomonas syringae EtHAn. During wheat–Pst interaction, Pst_9302 overexpression suppressed reactive oxygen species (ROS) accumulation and cell death caused by the avirulent Pst race CYR23. The host-induced gene silencing (HIGS) of Pst_9302 resulted in decreased Pst pathogenicity with reduced infection area. The results suggest that Pst_9302 plays a virulence role in suppressing plant immunity and promoting Pst pathogenicity. Moreover, wheat voltage-dependent anion channel 1 protein (TaVDAC1) was identified as candidate Pst_9302-interacting proteins by yeast two-hybrid (Y2H) screening. Pull-down assays using the His-Pst_9302 and GST-TaVDAC1 protein verified their interactions. These results suggest that Pst_9302 may modulate wheat TaVDAC1 to regulate plant immunity.